2017
DOI: 10.3847/1538-4357/aa8d1a
|View full text |Cite
|
Sign up to set email alerts
|

The Three-part Structure of a Filament-unrelated Solar Coronal Mass Ejection

Abstract: Coronal mass ejections (CMEs) often exhibit the typical three-part structure in the corona when observed with white-light coronagraphs, i.e., the bright leading front, dark cavity, and bright core, corresponding to a high-lowhigh density sequence. As CMEs result from eruptions of magnetic flux ropes (MFRs), which can possess either lower (e.g., coronal-cavity MFRs) or higher (e.g., hot-channel MFRs) density compared to their surroundings in the corona, the traditional opinion regards the three-part structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 67 publications
4
27
0
Order By: Relevance
“…The elemental compositions within ICMEs are determined by many factors, such as the properties of source regions and the detailed eruption processes (Song and Yao, 2020). In the meantime, many CMEs possess the three-part structure (Vourlidas et al, 2013;Song et al, 2017bSong et al, , 2019a that result from filament or hot channel eruptions. The different parts of CMEs could contain different FIP biases and thermodynamic evolution from the Sun.…”
Section: The Large Standard Deviationmentioning
confidence: 99%
“…The elemental compositions within ICMEs are determined by many factors, such as the properties of source regions and the detailed eruption processes (Song and Yao, 2020). In the meantime, many CMEs possess the three-part structure (Vourlidas et al, 2013;Song et al, 2017bSong et al, , 2019a that result from filament or hot channel eruptions. The different parts of CMEs could contain different FIP biases and thermodynamic evolution from the Sun.…”
Section: The Large Standard Deviationmentioning
confidence: 99%
“…The CME cores used to be interpreted as eruptive filaments (Gilbert et al 2000). However, Song et al (2017) performed a statistical work based on looking into 42 CMEs with three-part structures and illustrated that 70% of the events are not associated with filaments. Theories for the CME front/leading edges are fairly involved and reviewed in Chen (2011) andWarmuth (2015).…”
mentioning
confidence: 99%
“…The cavity and core have been considered as the MFR cross section and erupted filament, respectively, for several decades. However, recent studies clearly demonstrated that both the filaments and hot channel MFRs can appear as the bright core [13][14][15][16]. The hot channels are first revealed through extreme ultraviolet passbands sensitive to high temperatures (e.g., 131 and 94 Å) [17], and they can also be observed in hard X-ray [18] and microwave [19] images.…”
Section: Introductionmentioning
confidence: 99%